FOAM REPLICATED POROUS 316L STAINLESS STEEL BASED ON TAGUCHI METHOD FOR BIOMEDICAL APPLICATIONS - Fazimah Mat Noor, 1981- author; Khairur Rijal Jamaludin, supervisor 582467; Sufizar Ahmad, supervisor 601238; Razak School of UTM in Engineering and Advanced Technology (UTM) (Kuala Lumpur : Universiti Teknologi Malaysia, 2018)
Thesis (Ph.D)-Universiti Teknologi Malaysia, 2018